The Role of STEM-Integrated Problem-Based Learning (PBL) Science Worksheets in Enhancing Critical Thinking Skills: A Literature Review (2015–2025) - Nasywa Dwi Kamila; Nurmala Mustofa; Naya Mahdiyya Sari; Rizka Isnaeni (Indonesian Journal of STEM Education, 2026)
The use of student worksheets based on problem-based learning integrated with STEM education represents an innovative approach to enhancing students’ critical thinking skills in science learning. However, systematic literature reviews specifically focusing on the integration of PBL and STEM within student worksheets remain limited. This article aims to analyze the role and effectiveness of PBL-STEM-based worksheets in improving critical thinking skills based on scientific publications from 2015 to 2025. The method employed is a systematic literature review (SLR) of 10 core articles identified using the Publish or Perish application. The analysis reveals that the integration of PBL and STEM in worksheets significantly enhances students’ critical thinking, with improvements ranging from moderate to high categories. The primary contributing factors include the use of contextual problem-solving activities, interdisciplinary learning approaches, and active student engagement. These findings confirm that science worksheets designed based on PBL-STEM, supported by investigative activities and interactive technology, are proven effective in developing higher-order thinking skills. The implications of this study highlight the importance of developing innovative and contextual learning materials to support 21st-century competencies.